PENGARUH KOMPETENSI, KOMUNIKASI DAN KOMPENSASI TERHADAP KINERJA KELOMPOK KERJA PADA UNIT LAYANAN PENGADAAN PEMERINTAH PROVINSI KALIMANTAN TIMUR - Heru Pratama (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this research is to measure and analyze the variables that become the main attention, which in this case, the influence of competence, communication, and compensation of the working group (pokja) performance on East Borneo Government Services Procurement Unit (ULP). Based on the research we can conclude that (1) Competence variable (X1), proven that it is statistically have significant influences to the performance variable (Y) of Working Group, (2) Communication variable (X2), proven that it is statistically have significant influences to the performance variable (Y) of Working Group, (3) Compensation variable (X3) statistically have significant influences to the performance variable (Y) of Working Group, (4) Simultaneously, competence variable (X1) and communication variable (X2) have significant influences to the performance (Y) of Working Group, (5) Simultaneously, competence variable (X1) and compensation variable (X3) have significant influences to the performance (Y) of Working Group, (6) Simultaneously, communication variable (X2) and compensation variable (X3) altogether have significant influences to the performance (Y) of Working Group, (7) In Anova table, we can see the significant value is 0,001 for the whole variable, therefore we can conclude that competence(X1), communication (X2), and compensation (X3) altogether have significant influence to the performance (Y) of Working Group in East Borneo Provincial Government ULP.